Fenomena Hikonka dalam Drama Dokushin Kizoku Karya Shimako Sato - Amada, I Gusti Bagus Reno; Indra Pradhana, Ngurah; Rauh Artana, I Nyoman (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2023)
This research is entitled "The Hikonka Phenomenon in the Drama Dokushin Kizoku by Shimako Sato". This study aims to determine the phenomena, causes and effects of hikonka as reflected in the drama Dokushin Kizoku by Shimako Sato.The method used in this research is descriptive analysis method. This study uses the theory of sociology of literature according to Wellek and Warren (2013) and the theory of semiotics according to Danesi (2010). Based on the results of the study, the hikonka phenomenon reflected in Shimako Sato's drama Dokushin Kizoku is depicted in several characters in the drama who are not married at an age that has passed the general limit. The factors that cause the hikonka phenomenon in the drama Dokushin Kizoku are (1) the factor of not believing in love, (2) deciding not to marry, (3) not being able to commit, (4) being more comfortable living alone, (5) don't want to have children.